Effects of Diurnal Variability on Essential Oil Composition of Sweet Basil (Ocimum basilicum L.) - Gurbuz, Bilal; Ipek, Arif; Basalma, Dilek; O. Sarihan, Ercument; Sancak, Cengiz; Ozcan, Sebahattin (Asian Journal of Chemistry, 2010)
Sweet basil (Ocimum basilicum L.) plants were grown under the field conditions and herb samples collected at the beginning of flowering stage. Herb samples were gathered at three different times in a day such as just before sunrise (6:00 h), midday (12:00 h) and after sunset (21:00 h), respectively. Essential oils obtained by hydrodistillation method of herb samples were analyzed by GS-MS. A total of 52 compounds were identified representing 93.34, 92.89 and 93.13% of total oil, respectively. Linalool (41.23%), α-cadinol (9.69%) and eugenol (5.37%) were found as major constituents. Essential oil ratios were recorded such as 0.67% at 6:00 h, 0.62% at 12:00 h and 0.74% at 21:00 h.